Culture and Technology Acculturation: Efforts to Revitalize the Prophetic Tradition in the Modern Worldview Era - Mufid, Abdul; Mufida, Nawal Miza; Ismail, Muhammad; Syaiful, Muhammad; Ilham, Agus (ADDIN, 2025)
This research explored the intersection between cultural heritage and technological progress in revitalizing and rejuvenating prophetic traditions. The research aimed to bridge the gap between traditional practices and contemporary challenges by utilizing the profusion of prophetic traditions, especially in Islamic teachings. Research questions included how technology can bridge the gap between traditional prophetic teachings and modern cultural contexts, what challenges and opportunities arise from this integration, and how revitalizing prophetic traditions through technology can contribute to cultural preservation and augmentation. Through a multidisciplinary approach with insights from cultural studies, religious studies, and technology, this research contributed to the ongoing discourse on preserving and revitalizing cultural heritage in the digital era. Research findings revealed that although technology offered new opportunities to revitalize prophetic traditions, such as through digital archives and social media, there were also challenges, including authenticity and cultural adaptation issues.